Chemical composition, cytotoxicity and in vitro antitrypanosomal and antiplasmodial activity of the essential oils of four Cymbopogon species from Benin - KPOVIESSI, Dossou Sika Salomé; Bero, Joanne; AGBANI, Pierre O.; Gbaguidi, A. Fernand; Kpadonou-Kpoviessi, Bénédicta; SINSIN, Brice; ACCROMBESSI, COFFI GEORGES; FREDERICH, Michel; MOUDACHIROU, Mansourou; QUETIN-LECLERCQ, Joëlle (My University, 2014)
Ethnopharmacological relevance: Cymbopogon species are largely used in folk medicine for the treatment of many diseases some of which related to parasitical diseases as fevers and headaches. As part of our research on antiparasitic essential oils from Beninese plants, we decided to evaluate the in vitro antiplasmodial and antitrypanosomal activities of essential oils of four Cymbopogon species used in traditional medicine as well as their cytotoxicity. Materials and methods: The essential oils of four Cymbopogon species Cymbopogon citratus (I), Cymbopogon giganteus (II), Cymbopogon nardus (III) and Cymbopogon schoenantus (IV) from Benin obtained by hydrodistillation were analysed by GC/MS and GC/FID and were tested in vitro against Trypanosoma brucei brucei and Plasmodium falciparum respectively for antitrypanosomal and antiplasmodial activities. Cytotoxicity was evaluated in vitro against Chinese Hamster Ovary (CHO) cells and the human non cancer ﬁbroblast cell line (WI38) through MTT assay to evaluate the selectivity. Results: All tested oils showed a strong antitrypanosomal activity with a good selectivity. Sample II was the most active against Trypanosoma brucei brucei and could be considered as a good candidate. It was less active against Plasmodium falciparum. Samples II, III and IV had low or no cytotoxicity, but the essential oil of Cymbopogon citratus (I), was toxic against CHO cells and moderately toxic against WI38 cells and needs further toxicological studies. Sample I (29 compounds) was characterised by the presence as main constituents of geranial, neral, β-pinene and cis-geraniol; sample II (53 compounds) by trans-pmentha-1(7),8-dien-2-ol, trans-carveol, trans-p-mentha-2,8-dienol, cis-p-mentha-2,8-dienol, cis-pmentha-1(7),8-dien-2-ol, limonene, cis-carveol and cis-carvone; sample III (28 compounds) by βcitronellal, nerol, β-citronellol, elemol and limonene and sample IV (41 compounds) by piperitone, (þ)-2-carene, limonene, elemol and β-eudesmol. Conclusions: Our study shows that essential oils of Cymbopogon genus can be a good source of antitrypanosomal agents. This is the ﬁrst report on the activity of these essential oils against Trypanosoma brucei brucei, Plasmodium falciparum and analysis of their cytotoxicity.
Keywords: Cymbopogon species Essential oils Chemical composition Antitrypanosomal activity Antiplasmodial activity Cytotoxicity